2012
DOI: 10.1158/1541-7786.mcr-12-0335
|View full text |Cite
|
Sign up to set email alerts
|

SUZ12 Promotes Human Epithelial Ovarian Cancer by Suppressing Apoptosis via Silencing HRK

Abstract: Epithelial ovarian cancer (EOC) ranks first as the cause of death for gynecological cancers in the United States. SUZ12 is a component of the polycomb repressive complex 2 (PRC2) and is essential for PRC2-mediated gene silencing by generating trimethylation on lysine 27 residue of histone H3 (H3K27Me3). The role of SUZ12 in EOC has never been investigated. Here we show that SUZ12 is expressed at significantly higher levels in human EOC (n=117) compared with either normal human ovarian surface epithelium (n=35,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
65
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 38 publications
6
65
0
1
Order By: Relevance
“…19 However, EZH2 is often overexpressed in EOCs. 7,8,18 In this study, we found that inhibition of EZH2 methyltransferase activity by GSK343 had little effect on the growth of human EOC cells in conventional 2D cultures (Fig. 1).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…19 However, EZH2 is often overexpressed in EOCs. 7,8,18 In this study, we found that inhibition of EZH2 methyltransferase activity by GSK343 had little effect on the growth of human EOC cells in conventional 2D cultures (Fig. 1).…”
Section: Discussionmentioning
confidence: 62%
“…It has previously been established that HRK, a pro-apoptotic PRC2/H3K27Me3 target gene, plays a key role in regulating apoptosis of EOC cells induced by decreasing H3K27Me3 levels in these cells. 18 Thus, we determined the effects of GSK343 on the expression of HRK in 2D vs. 3D cultures. Indeed, we observed a significant upregulation of HRK in EOC cells treated with GSK343 in 3D cultures but not in 2D cultures (Fig.…”
mentioning
confidence: 99%
“…SUZ12 has been involved in both histone methyltransferase activity and the silencing function of the EED-EZH2 complex [2]. SUZ12 is hard to detect in normal tissues but amplified and overexpressed in several human cancers, such as oarian cancer, mantle cell lymphoma or breast cancer [3,4,5]. There is increasing evidence showes that SUZ12 plays an important role in carcinogenesis by acting as an oncogene, such as stimulates cell proliferation, blocks apoptosis, and promotes cell invasion and metastasis [3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…PRC2/EZH2 target genes are highly enriched for pathways that regulate stem cell pluripotency, cell proliferation, and oncogenic transformation (Kleer et al, 2003; Ting et al, 2006; Jones and Baylin, 2007; Schwartz and Pirrotta, 2007; Jaenisch and Young, 2008; Li et al, 2012a). Not surprisingly, components of PRC2 are often over-expressed in human cancers and their expression often positively correlates with aggressiveness in these diseases (Varambally et al, 2002; Kleer et al, 2003; Li et al, 2010, 2012b). In addition, gain-of-function mutations in EZH2 have also been reported in certain hematopoietic malignancies (Ryan et al, 2011; Majer et al, 2012).…”
mentioning
confidence: 99%
“…In addition, gain-of-function mutations in EZH2 have also been reported in certain hematopoietic malignancies (Ryan et al, 2011; Majer et al, 2012). Notably, it has been shown that EZH2 and other components of PRC2 play a key role in regulating proliferation, apoptosis, and invasion of human EOC cells (Li et al, 2010, 2012b; Lu et al, 2010). In addition, EZH2 regulates EOC microenvironment by enhancing angiogenesis (Lu et al, 2010).…”
mentioning
confidence: 99%